AI-Driven Enhancements for Secure API Gateways in Cross-Platform Data Integration Architectures (Journal of Artificial Intelligence Research, 2023)
The proliferation of cross-platform data integration architectures has necessitated the enhancement of security mechanisms for Application Programming Interfaces (APIs). As businesses increasingly rely on APIs to facilitate communication between disparate systems, ensuring the security of these APIs becomes critical. Artificial Intelligence (AI) has emerged as a transformative technology capable of improving the security of API gateways by identifying vulnerabilities, detecting malicious activities, and automating the enforcement of security policies. This paper explores AI-driven solutions for enhancing the security of API gateways in cross-platform data integration architectures. The paper discusses how AI techniques, such as machine learning (ML) and anomaly detection, can be integrated into API gateway frameworks to provide proactive security measures. Furthermore, it examines the role of AI in managing access control, monitoring API traffic, and preventing common security threats such as API abuse, DDoS attacks, and data breaches. The challenges of implementing AI-driven security measures in API gateways are also addressed, including the need for high-quality data, model training, and integration with existing security infrastructures. Finally, the paper highlights real-world applications and case studies, demonstrating the effectiveness of AI-driven API security solutions in practice.
Keywords: AI-driven security; API gateways; cross-platform data integration